Prognostic Value of Right Ventricular Ejection Fraction Assessed by 3D Echocardiography in COVID-19 Patients - Zhang, Yanting; Sun, Wei; Wu, Chun; Zhang, Yiwei; Cui, Li; Xie, Yuji; Wang, Bin; He, Lin; Yuan, Hongliang; Zhang, Yongxing; Cai, Yu; Li, Meng; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: RVEF (right ventricular ejection fraction) measured by three-dimensional echocardiography (3DE) has been used in evaluating RV function and can provide useful prognostic information in other various cardiovascular diseases. However, the prognostic value of 3D-RVEF in coronavirus disease 2019 (COVID-19) remains unknown. We aimed to investigate whether 3D-RVEF can predict the mortality of COVID-19 patients. Methods: A cohort of 128 COVID-19-confirmed patients who had undergone echocardiography were studied. Thirty-one healthy volunteers were also enrolled as control. COVID-19 patients were divided into three subgroups (general, severe and critical) according to COVID-19 severity-of-illness. Conventional RV (right ventricular) structure and function parameters, RV free wall longitudinal strain (FWLS) and 3D-RVEF were acquired. RVFWLS was measured by two-dimensional speckle tracking echocardiography. RVEF was acquired by 3DE. Results: Compared with controls, 2D-RVFWLS and 3D-RVEF were both significantly decreased in COVID-19 patients (-27.2±4.4% vs -22.9±4.8%, P<0.001; 53.7±4.5% vs 48.5±5.8%, P<0.001). Critical patients were more likely to have a higher incidence of acute cardiac injury and acute respiratory distress syndrome (ARDS), and worse prognosis than general and severe patients. The critical patients exhibited larger right-heart chambers, worse RV FAC, 2D-RVFWLS and 3D-RVEF and higher proportion of pulmonary hypertension than general and severe patients. Eighteen patients died during a median follow-up of 91 days. The multivariate Cox regression analysis revealed the acute cardiac injury, ARDS, RV fractional area change (FAC), RVFWLS and 3D-RVEF were independent predictors of death. 3D-RVEF (chi-square to improve 18.3; P< 0.001), RVFAC (chi-square to improve 4.5; P=0.034) and 2D-RVFWLS (chi-square to improve 5.1; P=0.024) all provided additional prognostic value of higher mortality over clinical risk factors. Moreover, the incremental predictive value of 3D-RVEF was significantly (P < 0.05) higher than RVFAC and RVFWLS. Conclusion: 3D-RVEF was the most robust independent predictor of mortality in COVID-19 patients and provided a higher predictive value over conventional RV function parameters and RVFWLS, which may be helpful to identify COVID-19 patients at a higher risk of death. Keywords: Three-dimensional echocardiography, Right ventricular function, Coronavirus disease 2019, Myocardial strain, Prognosis